Teachers’ Efforts in Growing Awareness of the Importance of Parents in Educating Children at SMP Muhammadiyah 5 Surakarta in Academic Year 2022/2023 - Nisa, Hany Khoirun; Isfihani, Isfihani; Praptiningsih, Praptiningsih (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the efforts made by teachers in raising awareness of the importance of parental involvement in educating children. This type of research is qualitative research with the research location of SMP Muhammadiyah 5 Surakarta, and the data collection techniques used are interviews, observations, and documentation. The results of this study indicate that the efforts made by teachers in fostering parental awareness are by building good communication with parents.